Differentiation of Tannat, Cabernet Sauvignon and Merlot grapes from Uruguay according to their general composition and polyphenolic potential - González-Neves, Gustavo; Ferrer, Milka; Gil, Graciela (Comunicata Scientiae, 2012)
This paper shows the results of a study carried out during four years (2001-2004). Its aim was the characterization of Tannat, Cabernet Sauvignon and Merlot grapes cultivated in the south of Uruguay. The results were evaluated to qualify the enological potential of these varieties of Vitis vinifera L. Typical cultivation situations in the region were included of each variety. The grapes were analysed at harvest for determination of global composition and polyphenolic potential. Tannat grapes presented very different characteristics in relation to other varieties. Tannat had the highest percentage of seeds, berry weight, sugar contents, total acidity, total polyphenols, total anthocyanins, extractable anthocyanins, skin tannins and seed tannins levels. Also, they had the lowest pH values and the highest EA%, corresponding to the lowest extractability of anthocyanins. The effect of vintage on the grape composition was very important, according to the impact of the climatic conditions in the synthesis of quality components of berries. However, the joint consideration of analytical indexes of base composition, polyphenolic potential and structure of the berry allowed a perfect discrimination of samples of each variety. Diferenciação de uvas Tannat, Cabernet Sauvignon e Merlot provenientes doUruguai de acordo com sua composição geral e potencial polifenólico Este trabalho apresenta os resultados de um estudo realizado durante quatro anos (2001-2004). Oobjetivo foi a diferenciação e caracterização de uvas de Tannat, Cabernet Sauvignon e Merlotcultivadas no sul do Uruguai. Os resultados foram avaliados para qualificar o potencial enológicodas variedades de Vitis vinifera L. em situações típicas de cultura na região. As uvas foram analisadasno momento da colheita para determinar a composição geral e o potencial polifenólico. Tannatapresenta características muito diferentes em relação às demais variedades. Tannat apresentouo maior percentual do peso da semente, peso das bagas, teor de açúcar, acidez total, polifenóistotais, antocianinas totais, antocianinas extraíveis, taninos da pele e taninos de sementes. Além disso,ela teve os menores valores de pH e maior EA%, correspondente a uma menor extractabilidadede antocianinas. O efeito da safra sobre a composição foi muito importante, de acordo com oimpacto das condições climáticas na síntese de componentes da qualidade dos frutos. No entanto,a análise conjunta da composição global, o potencial de polifenóis e a estrutura da baga permitiuuma perfeita discriminação das amostras de cada variedade.